Analisis ANALISIS SERANGAN DHCP STARVATION ATTACK PADA ROUTER OS MIKROTIK - Tamsir Ariyadi; Aidil Nur Riyansyah; M Agung; M. Alzi Ikrar (JURNAL ILMIAH INFORMATIKA, 2023)
Dynamic Host Configuration Protocol (DHCP) is a client-server protocol that functions to provide IP addresses to client computers/network devices automatically. In using the Mikrotik OS, do further analysis regarding the attack on the DHCP starvation attack. Where the attacker will become a host on one of the computers and request an IP to the proxy OS to obtain the client's personal information which will then be recorded and analyzed for the Man in the Middle attack. Of course, this can be prevented by the filtering techniques available on the miktorik OS. Of course this can be prevented by the filtering techniques that exist on the proxy OS. The key can be seen on the hostname computer that is registered on the proxy, so that in the DHCP Discover process which asks for an IP on the proxy DHCP Server, if the hostname is not registered, it will be listed as Dynamic Host Configuration Protocol (DHCP), which is a client-server protocol that functions to provide IP addresses to client computer/network device automatically. In using the Mikrotik OS, do further analysis regarding the attack on the DHCP starvation attack. Where the attacker will become a host on one of the computers and request an IP to the proxy OS to obtain the client's personal information which will then be recorded and analyzed for the Man in the Middle attack. Of course, this can be prevented by the filtering techniques available on the miktorik OS. Of course this can be prevented by the filtering techniques that exist on the proxy OS. The key can be seen on the hostname computer that is registered on the proxy, so that in the DHCP Discover process which asks for an IP on the proxy DHCP Server, if the hostname is not registered, it will be listed for blocking.